UPAYA KEPALA SEKOLAH MENINGKATKAN KEMAMPUAN GURU MATEMATIKA DALAM MENYUSUN SOAL HOTS MELALUI BIMBINGAN INDIVIDUAL DI SMAN 2 PRINGSEWU - Siregar, Jahara (LPPM STKIP PGRI Bandar Lampung, 2019)
The purpose of this study is to improve the teachers’ ability of SMAN 2 Pringsewu in preparing HOTS questions through individual guidance. This research was conducted in the even semester in 2018/2019 academic year with a total of 6 mathematics subjects. Data collecting technique used were questionnaires and observation instruments about the assessment tools. The result of Preliminary research indicated that the teacher does not understand what HOTS is about its characteristics and how to arrange it. After the implementation of individual guidance in the first cycle for the preparation and development of HOTS questions from 6 teachers obtained an average value of 85 and the results of the questionnaire about the attitudes of teachers towards individual guidance 83.33% agreed and 16.67% were still in doubt. This showed a positive attitude for the teacher towards individual guidance. From the second cycle the results of the study for the preparation and development of HOTS questions obtained an average value of 94% of questionnaires on the positive attitude of the teacher in the second cycle increased to 100% agreeing to the guidance model through individual guidance. This shows a very significant increase.